Management of Winery Wastewater by Re-using it for Crop Irrigation - A Review - Howell, C.L.; Myburgh, P.A. (South African Journal of Enology and Viticulture, 2018)
In South Africa, grapes are an important crop in the Western and Northern Cape Provinces. The wine industry makes a significant contribution to the economy in these regions. Wineries generate large volumes of poor quality wastewater, particularly during harvest. Information on actual amounts of water used by wineries is limited and appears to be inconsistent. Usually most of the raw water entering wineries ends up as wastewater. Winery wastewater has high levels of chemical oxygen demand (COD) and contains high levels of K+ and Na+. There is considerable variation in wastewater quality parameters between wineries, as well as a strong seasonal variation. In most cases, the wastewater is used for irrigation of small permanent pasture grazing paddocks. The use of winery wastewater for vineyard irrigation could have many potential benefits for the wine industry. Irrigation with wastewaters containing high levels of K+ could be beneficial to soil fertility, although long-term application could have negative effects on soil chemical properties. In terms of South African guidelines, wineries must register their intended wastewater use with the Department of Water and Sanitation. The quantity of wastewater irrigated on a weekly basis has to be monitored and wastewater quality measured monthly. Weekly water balances should be drawn up with the assistance of a soil scientist. When selecting crops for irrigation with winery wastewater, soil characteristics and climatic conditions as well as wastewater quality and quantity should be considered. It is important to quantify soil chemical responses to application of winery wastewater every three months.